Prospects of low and zero-carbon renewable fuels in 1.5-degree net zero emission actualisation by 2050: a critical review - Anika, Ogemdi Chinwendu; Nnabuife, Somtochukwu Godfrey; Bello, Abdulrauf; Okoroafor, Esuru Rita; Kuang, Boyu; Villa, Raffaella (Elsevier, 2022)
The Paris Climate Agreement seeks to keep global temperature increases under 2° Celsius, ideally 1.5° Celsius. This goal necessitates significant emission reductions. By 2030, emissions are expected to range between 52 and 58 GtCO2e from their 2016 level of approximately 52 GtCO2e. This review paper explores a number of low and zero-carbon renewable fuels, such as hydrogen, green ammonia, green methanol, biomethane, natural gas, and synthetic methane (with natural gas and synthetic methane subject to CCUS both at processing and at final use) as alternative solutions for providing a way to rebalance transition paths in order to achieve the goals of the Paris Agreement while also reaping the benefits of other sustainability targets. The results show renewables will need to account for approximately 90% of total electricity generation by 2050 and approximately 25% of non-electric energy usage in buildings and industry. However, low and zero-carbon renewable fuels currently only contributes about 15% to the global energy shares, and it will take about 10% more capacity to reach the 2050 goal. The transportation industry will need to take important steps toward energy efficiency and fuel switching in order to achieve the 20% emission reduction. Therefore, significant new commitments to efficient low-carbon alternatives will be necessary to make this enormous change. According to this paper, investing in energy efficiency and low-carbon alternative energy must rise by a factor of about five by 2050 in comparison to 2015 levels if the 1.5 °C target is to be realised.
Keywords: Renewable fuels; Carbon dioxide (CO2); Net zero emissions (NZE)